Effect of COVID-19 lockdown measures on the plastic waste generation trends and distribution of microplastics in the Northwestern Arabian/Persian Gulf - Al-Salem, S. M.; Al-Osairi, Yousef; Constantinou, Achilleas (My University, 2022)
Microplastics (MPs) have been recognised as a persistent pollutant within environmental sinks, classed as a pollutant of priority in the Basel, Rotterdam and Stockholm (BRS) Conventions. In this work, we relate one of the longest COVID-19 recent pandemic lockdowns enforced in the State of Kuwait to the plastic waste generation and MPs accumulation which were released from a selected site known for leisure and fishing activities on the Northwestern part of the Arabian/Persian Gulf. After 15 days from the release, the coverage area was the widest for the distribution and transport plume of MPs. The particles were retained at known areas for fishing activities in Kuwait and were controlled by the hydrodynamics of the modelling configuration rather than the MPs release strength (i.e., number of particles). Moreover, during the period between January to April 2020; the MPs covered almost a double dispersed area which was linked to the hydrodynamics of the release model exercise. Generally, the most affected areas of the MPs distribution were along the Kuwait City coastline and the COVID-19 lockdown measures didn't affect the MPs particle distribution as much as environmental conditions.
Keywords: Microplastics; COVID-19; Plastic waste; Numerical modelling; Gulf